Investigação dos níveis de 25 (OH) D e suplementação de vitamina D3 em pacientes com vitiligo - Meneses, Daniele de Vasconcelos Cerqueira (2019)
Vitiligo is a disease characterized by unpigmented spots with different well-demarcated shapes and sizes. It is caused by the destruction of functional melanocytes in the epidermis and is considered an autoimmune disorder. Among the treatments used in vitiligo, vitamin D plays a role in increasing innate immunity associated with profound regulation of acquired immunity, increasing tyrosinase activity and melanogenesis through the vitamin D receptor (VDR) in melanocytes. This study aimed to conduct a cross-sectional study to investigate the 25 (OH) D levels of patients diagnosed with vitiligo compared with healthy individuals and a pilot clinical trial of vitamin D3 supplementation in patients with vitiligo volunteers from the dermatology outpatient clinic. HU-UFS. A narrative review was performed on the relationship between vitamin D and vitiligo where a search was performed in the databases Pubmed, Web of Science, Scopos and Lilacs published until May 2019. For the cross-sectional study, 61 individuals entered, in which Blood collection was performed to verify 25 (OH) D levels, determination of skin pigmentation and affected body surface area. The pilot clinical trial included 12 patients diagnosed with vitiligo, where they were divided into two groups: group A receiving 35000 IU / day vitamin D3 and group B receiving placebo. Vitamin D3 supplementation lasted 6 months. Statistical analysis used Fisher's exact test and Chi-square test; Monte Carlo; Mann-Whitney test; Spearman correlation and bivariate ANOVA. The cross-sectional study sample consisted of 68.8% women and 31.2% men in the vitiligo group and 75.9% women and 24.1% men in the control group. The mean 25 (OH) D levels were 32.1 ng / mL and 33.7 ng / mL in the vitiligo and control group respectively. In the pilot clinical study, 83.3% of the patients were female and 17.7% male. The mean 25 (OH) D levels after 90 days of treatment were 78.6 ng / mL and 39.5 ng / mL in group A and B, respectively. The average MRI after 90 days of treatment was 32.7% and 12.5% in group A and B, respectively. We found no statistical difference in the 25 (OH) D levels of vitiligo patients compared to healthy subjects. Levels of 25 (OH) D increased in group A. Pigmentation stabilized in patients receiving vitamin D3.